2016
DOI: 10.1002/adma.201603154
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High‐Performance Ternary Organic Solar Cells through Tuning Acceptor Alloy

Abstract: Acceptor alloys based on n-type small molecular and fullerene derivatives are used to fabricate the ternary solar cell. The highest performance of optimized ternary device is 10.4%, which is the highest efficiency for one donor/two acceptors-based ternary systems. Three important parameters, J , V , and FF, of the optimized ternary device are all higher than the binary reference devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(131 citation statements)
references
References 36 publications
9
120
0
1
Order By: Relevance
“…As observed from Figure 2 and Table 1, the PTB7-Th:PC 70 BM presented a PCE value of 8.8%, a V oc of 0.782 V, J sc of 16.54 mA cm −2 , and FF of 67.2%, respectively. These results are similar to those reported by other research groups, [31,40,54] suggesting that the incorporation of crystalline molecule could facilitate the fabrication of PTB7-Th:PC 70 BM-based devices with thick active layer suitable for large-area printing. A similar trend of FF change versus DRCN5T ratio was also observed.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As observed from Figure 2 and Table 1, the PTB7-Th:PC 70 BM presented a PCE value of 8.8%, a V oc of 0.782 V, J sc of 16.54 mA cm −2 , and FF of 67.2%, respectively. These results are similar to those reported by other research groups, [31,40,54] suggesting that the incorporation of crystalline molecule could facilitate the fabrication of PTB7-Th:PC 70 BM-based devices with thick active layer suitable for large-area printing. A similar trend of FF change versus DRCN5T ratio was also observed.…”
Section: Resultssupporting
confidence: 91%
“…[25] Although both ternary OSCs and tandem OSCs could improve the power conversion efficiency (PCE) value to about 15%, the ternary strategy possessing simplicity of processing active layer exhibits great potential in R2R technology. [29] Especially, many researchers have realized the importance of miscibility in ternary OSCs, [28,[35][36][37] such as the appearance of Förster resonance energy transfer, [38] distribution of third additive on the interfaces of donor and acceptor, [39] formation of alloy with donor or acceptor, [36,37,40] etc. [6,[32][33][34] Unfortunately, most of the research work about how to select appropriate third additive is based on the trial and error strategy, which is a process of labor and time consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the morphological analysis, it is clearly demonstrated that the ternary morphology stabilization originates from two important elements. [78] Zhan and co-workers. Second, the suppression of the IEICO-4F crystals in the aged ternary devices, unlike in the binary blend, is an indication that the PC 71 BM dispersion in IEICO-4F is highly stable, and we attribute this to formation of acceptor alloys, which provide additional entropy.…”
Section: Discussionmentioning
confidence: 99%
“…As will be detailed later, the interfacial tension between two organic molecules has been demonstrated to correlate with the extent of mixing. [15,22,63,[71][72][73][74] Second, the FF of the devices increases first and then drops with increasing IEIC-Th content. There are a few clear trends in the J-V characteristics of the PTFB-O:ITIC-Th:IEIC-Th ternary devices.…”
Section: Ternary Blend Design and Photovoltaic Device Performancementioning
confidence: 97%
“…[11,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] However, one main constraint that slows down the development of ternary OSC is the difficulty in controlling the morphology of ternary blends. To maintain the simplicity of the single junction structure and in the meantime broaden the absorption range of the solar cell, ternary OSCs have been developed where two donors and one acceptor or one donor and two acceptors are blended together to form the active layer.…”
mentioning
confidence: 99%